Extending Financialisation and Increasing Fragility of the Financial System - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2013)
Financialisation is a complex and dynamic process of enlarging the monetary and financial relations in economy and society. This paper deals with the analysis of the financial market structure such as: the role and magnitude of financial sectors, the dynamics of the banking sector versus the stock market and the rising role of the shadow banking sector. Also it explains and analyses the ways and modalities to develop financialisation by growing the public and private indebtedness, extension of the securitisation process and using the financial derivatives on a large scale. Considered endogenous factors, they all increase the fragility of the financial system.
Keywords: E44; G01; G18; G23; G24; G28; G32; 330; financialisation; financial sector; stock market; shadow banking; indebtedness; financial innovation; securitisation; financial derivatives